A Validated RP-HPLC Method for Simultaneous Estimation of Antidiabetic Drugs Pioglitazone HCl and Glimepiride (Bangladesh Pharmaceutical Journal, 2013)
A simple, fast and economic reversed phase high performance liquid chromatographic (RP-HPLC) method has been developed and validated for simultaneous and quantitative analyses of pioglitazone HCl and glimepiride in pharmaceutical dosage forms. The method was developed using the mobile phase comprising of potassium dihydrogen phosphate buffer (KH2PO4) at pH 3.4 and acetonitrile in the ratio of 40:60 (v/v) over C-18 bonded silica column (250 x 4.6 mm, 5 um, Phenomenex Inc.) at ambient temperature. The flow rate was at 0.8 min/min and the eluent was monitored by UV detection at 235 nm. The recoveries were found to be >97% for pioglitazone and >99% for glimepiride, demonstrative of accuracy of the protocol. Inter-day and intra-day precision of the new method were less than the maximum allowable limit (RSD% ? 2.0) according to ICH, USP and FDA guidelines. The method showed linear response with correlation coefficient (r2) values of 0.9991 for pioglitazone and 0.9999 for glimepiride. Therefore, the method was found to be accurate, reproducible, sensitive and less time consuming and can be successfully applied for the assay of pioglitazone and glimepiride in combined formulations. DOI: http://dx.doi.org/10.3329/bpj.v16i1.14497 Bangladesh Pharmaceutical Journal 16(1): 69-75, 2013